Atypical ectopic pregnancy: a nightmare for the gynaecologist - Bhardwaj, Bikram; Menon, Aruna; Nandy, Souvik; ., Santosh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Ectopic pregnancy is one of the leading causes of maternal morbidity and mortality in early pregnancy. Incidence of ectopic pregnancy is 2% of total reported pregnancies and is rising in the recent past due to increase in RTIs and STIs and even early diagnosis due to advancing technology. Classical triad of pain abdomen, bleeding p/v and amenorrhea is not present in all the cases which add to confusion in diagnosing these atypical presentations. A meticulous history and clinical examination along with combination of transvaginal ultrasound (TVS) and serum beta HCG levels (discriminatory zone) can aid in picking up these atypical cases as depicted in our study. Here, we discussed 7 cases of atypical presentations of ectopic pregnancy which reported to gynaecology OPD of a service hospital of armed forces in a span of 3 months. One patient had pregnancy test negative, one patient was repeatedly treated as a case of AUB, 2 cases of heterotopic pregnancies, 1 case of elderly cornual ectopic and 2 young cases reporting one with repeated episodes of gastritis and other with post tubectomy status. The cases were managed accordingly using surgical methods. Ectopic pregnancy is like a tornado which if not diagnosed in time may prove fatal. Atypical presentation of ectopic pregnancies not fitting into the well-known triad of ectopic pregnancies these days add to confusion. One really needs to be ectopic minded if we actually want to avoid this catastrophe & save these young mothers.